South Africa milestones to achieving the sustainable development goals on poverty and hunger - Fofana, Ismaël; Chitiga-Mabugu, Margaret; Mabugu, Ramos (International Food Policy Research Institute, 2018)
South Africa has signed the Sustainable Development Goals (SDGs) and placed poverty and inequality reduction at the forefront of its National Development Plan. This study links a nonparametric income distribution (micro) simulation model and an economywide general equilibrium (macro) model to define the milestones South Africa must meet to halve poverty and end hunger by 2030 as targeted by the SDGs. The current economic growth of 2.0 percent on average annually must be accelerated to 4.5 percent between 2015 and 2030 to achieve the SDGs on poverty and hunger. Although an income growth strategy is important to reduce hunger, an income redistribution strategy of expanding social assistance to cover 10 percent of the population—that is, nearly 7 million persons—appears to be a key to ending hunger by 2030. Rural areas should be targeted for intervention to reduce income inequality. Skilled and high-skilled labor markets offer better employment and earning opportunities in these geographic areas than do the markets for other skill levels. Thus, skill development programs in these areas are likely to contribute to meeting the SDGs on poverty and hunger by 2030.